Penelitian Sejarah Hukum Sipil di Indonesia - Khumarga, Dahnial (LAW REVIEW, 2002)
The Indonesian Civil Law - which was derived from the Dutch one-is supposed to be the lee generalis of the (Indonesian) Commercial Law Respectively is supposedly the Business Law to the Civil Law as well Commercial Law. Take as example for instance the Law of contract. Which is the main source of the Business Law. Therefore its no  eraggeration to say that a Business Law scholar thould be a "civilist" as prerequisite.  Indonesia, which historically belongs to the Roman Civil Law Tradition Country, is best to make every effort in tracing the historical background of the Legal System concerned. On the other hand it is also expected that the "counterpart", e.g. the Common Law Tradition should be made a study as well, which secently has been influencing the  development of the Indonesian has system quite significantly, especially in the field of  Business Law. By having the knowledge of the history of the Roman Civil Law, hopefully it will be of much benefit to the Business Law scholars and observers.